Desarrollo de la psicomotricidad en el proceso de la lectoescritura de los estudiantes del 3er año de Educación General Básica - Arana Calvache, Alexandra Elizabeth (2020)
The main purpose of this research work is to analyze the development of psychomotricity in the process of literacy for students of the 3rd year of basic general education in the Educational Unit "Anne Sullivan" in the 2019-2020 school period, based on a problem Notorious in psychomotricity, where, it has not been stimulated, therefore, it causes problems of low performance in reading and writing. In this research, its approach is relatively mixed, the combination of two qualitative and qualitative methods, the type of research is descriptive in the field and bibliographic, whose methods are inductive and deductive, a sample of 8 students was taken, 8 parents of family and 6 teachers of the elementary and middle basic sublevels. In order to obtain information that contributes to this work, it was necessary to apply an observation form to the students to know exactly the student's learning problems; In addition, a survey was applied to teachers, an interview with the directors and parents, to obtain information on the study variables…………